Pembinaan Keagamaan Oleh Rohaniawan Khonghucu di Tuban Jawa Timur - Joko Tri Haryanto (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
Religious life of Confucianist can not be separated from the role of Churchman.Churchman of Confucius held some development of religious life consistingof religiosity, ritual and social aspect. This is a qualitative research describing religious development held by Churchman of Confucius in Tuban East Java. In the aspect of religiosity, Churchmen focuses their program on faith building and religious value building. Churchman become a leader, andthey responsible on religious ceremony whether in the public worship or on the ceremony of life circle, for instance, marriage and death ceremony. On the social aspect, churchman educate their followers about moral value and socialvalue.